Industri perkebunan kapas Asembagus, Situbondo tahun 1945-1997 - Sri Indah Damayanti; R. Reza Hudiyanto (Historiography: Journal of Indonesian History and Education, 2022)
Cotton is a plantation crop that is planted once a year during the dry season in Indonesia. Cotton plant (Gossypium sp.) is a shrub plant which produce fiber from the fruit, this fiber used as the main raw material in textile manufacturing. This study will discuss about the beginning of the establishment of cotton plantation industry in Asembagus, Situbondo. How the dynamics relationship between cotton development institutions such as cotton mills, cotton experimental gardens and community cotton plantations in the 1945-1997 and their impact on the community in Asembagus District of Situbondo Regency. The title was chosen because Asembagus District of Situbondo Regency famous as center of planting and developing cotton commodities in Java Island since independence of the republic of Indonesia in 1945 until the decline of cotton commodities in Asembagus at the end of the Repelita program around 1997.This study used historical research methods that is topic selection, heuristics, source criticism and verification, interpretation, and historiography by searching written sources such as archives, books and previous research nor oral sources obtained by observation and literature review. From the data collected, it indicates that there is an imbalanced (dualism) in the production activities of the Asembagus cotton plantation industry, This gap has had a chain effect that led to the discontinuity of cotton cultivation in Asembagus, Situbondo. Kapas adalah tanaman perkebunan yang ditanam satu kali setahun yaitu saat musim kemarau di Indonesia. Tanaman kapas (Gossypium sp.) merupakan tanaman jenis semak yang menghasilkan serat melalui buahnya, serat inilah yang menjadi bahan baku utama dalam pembuatan tekstil. Studi ini akan membahas mengenai awal mula berdirinya industri perkebunan kapas di Asembagus, Situbondo. Bagaimana dinamika hubungan antara lembaga pengembangan kapas yaitu pabrik penggilingan kapas, kebun percobaan kapas Asembagus dan perkebunan kapas rakyat pada tahun 1945-1997 serta dampaknya bagi masyarakat di Kecamatan Asembagus, Kabupaten Situbondo. Judul tersebut dipilih karena Kecamatan Asembagus, Kabupaten Situbondo terkenal sebagai pusat penanaman dan pengembangan komoditas kapas di Jawa sejak masa Kemerdekaan Republik Indonesia tahun 1945 hingga mundurnya komoditas kapas di Asembagus pada akhir program Repelita sekitar tahun 1997. Studi ini menggunakan metode penelitian sejarah yaitu pemilihan topik, heuristik, kritik atau verifikasi, interpretasi dan historiografi dengan melakukan penelusuran sumber tertulis berupa arsip, artikel, buku dan penelitian terdahulu serta sumber lisan yang didapatkan melalui observasi, studi pustaka. Dari data-data yang terkumpul mengindikasikan adanya ketimpangan (dualisme) pada kegiatan produksi Industri perkebunan kapas Asembagus, ketimpangan ini memberikan dampak berantai hingga menyebabkan terhentinya penanaman kapas di Asembagus, Situbondo.